2022
DOI: 10.3390/en15062258
|View full text |Cite
|
Sign up to set email alerts
|

Energy Sustainability on an Offshore Island: A Case Study in Taiwan

Abstract: This study determines the energy usage pattern for Penghu, which is an island in the Taiwan Strait, for which electricity is the major energy source. There is an increase in electricity consumption as the number of inhabitants and tourists increases. Water supply from desalination plants represents another major electricity demand. To reduce energy consumption and carbon emissions, subsidy programs are used to encourage the use of LED lighting and energy-efficient appliances (air conditioners and refrigerators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Low-carbon development is an important measure to reduce environmental degradation due to increased economic activity [43][44][45][46]. Recent studies [47] have shown that reducing carbon emissions increases the productivity and brand value of the hotel chains studied.…”
Section: Introductionmentioning
confidence: 99%
“…Low-carbon development is an important measure to reduce environmental degradation due to increased economic activity [43][44][45][46]. Recent studies [47] have shown that reducing carbon emissions increases the productivity and brand value of the hotel chains studied.…”
Section: Introductionmentioning
confidence: 99%